2022
DOI: 10.3390/toxics10070348
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticles Induce DNA Damage in Sand Dollar Scaphechinus mirabilis Sperm

Abstract: Products containing nanomaterials are becoming more and more common in everyday life. Zinc oxide nanoparticles (ZnO NPs), meanwhile, are among the most widely used NPs. However, their genotoxic effect on the germ products of marine organisms is poorly understood. Therefore, the effects of ZnO NPs and zinc ions (20, 50, 100, 200 µg/L) on the sperm of sand dollar Scaphechinus mirabilis were compared. Comet assay showed that both tested pollutants caused an increase in DNA damage to 6.57 ± 2.41 and 7.42 ± 0.88% D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…However, the reason for the antagonism between nAg and nCuO remains unclear. DNA damage was also increased in the sperm of the sand dollar Scaphechinux mirabilis exposed to zinc oxide nanoparticles and zinc ions indicating that DNA damage could be produced by both the nanoparticle and dissolved zinc [ 43 ]. However, dissolved Zn did not change with the treatment groups and was not correlated with DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reason for the antagonism between nAg and nCuO remains unclear. DNA damage was also increased in the sperm of the sand dollar Scaphechinux mirabilis exposed to zinc oxide nanoparticles and zinc ions indicating that DNA damage could be produced by both the nanoparticle and dissolved zinc [ 43 ]. However, dissolved Zn did not change with the treatment groups and was not correlated with DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies in the literature reported that some biosynthesized ZnO NPs may have hazardous potential on living organisms and the environment (Dimkpa et al, 2012; Song et al, 2014; Zukiene and Snitka, 2015). Additionally, recent findings revealed genotoxic potentials of ZnO NPs, resulting in genomic instabilities and/or epigenetic alterations, which eventually translated into a variety of diseases (Akbaba and Türkez, 2018; Kukla et al, 2022; Srivastav et al, 2017). In this context, the genotoxic potentials of the NPs synthesized in our study were also investigated with the Ames/ Salmonella , E. coli WP2, Yeast DEL, seed germination, and RAPD assay systems.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive and developmental toxicity are crucial components of overall toxicology and have received increasing attention in recent years . If exogenous substances are injected into the body of a male animal, it may adversely affect sperm quality, motility, and testicular morphology, thereby reducing fertility and affecting the health of offspring. Several studies have demonstrated a decline in animal reproductive output after exposure to nickel, , gold nanoparticles, nano-titanium dioxide (TiO 2 ), silicon dioxide (SiO 2 ) nanoparticles, and carbon nanotubes …”
Section: Introductionmentioning
confidence: 99%